The history of the Holy Mar Maʿin with a guide to the Persian martyr acts - Brock, Sebastian P. (Persian martyr acts in Syriac, 2008)
Introduction and outline -- Synopsis -- Literary models -- Date of composition : the linguistic evidence -- Fiey's dating of the life -- Topography -- The chronological data -- Historicity -- The manuscript -- The present edition -- Apparatus -- Translation -- Annotation -- A guide to the Persian martyr acts -- Syriac texts -- Under Vahran II (276-293) -- Under Shapur II (309-379) -- Late fourth century -- Under Yazdgard I (399-420) -- Under Vahram V (421-438) -- Under Yazdgard II (439-457) -- Late fifth century -- Under Khosro I (531-579) -- Under Khosro I/Hormizd iv/khosro II -- Under Khosro II (591-628) -- Concordance with Bedjan, AMS II and IV -- Early manuscripts -- Greek translations -- Personal names, excluding biblical -- Biblical personal names -- Place names (alphabeticized according to the Syriac alphabet) -- Names of Persian martyrs listed at the end of British Library, add. 12,150 (copied in Edessa and dated November, AD 411)